Awareness of existence, knowledge, and acceptability of HIV pre-exposure prophylaxis (PrEP) among university students in Thailand - Tiwaphon Thongsutt, Sawitree Laopaiboonkun, Nisakorn Thanon, Virasinee Thongthummachart, Areena Yaena, Fares M. S. Muthanna, (Journal of Applied Pharmaceutical Science, 2022)
Despite the fact that teenagers in South Thailand have higher rates of human immunodeficiency virus (HIV) infection, little is known about HIV pre-exposure prophylaxis (PrEP), which is considered one of the prevention strategies suggested to control HIV illness. PrEP is a once-daily pill that has been shown to be more than 90% effective in HIV prevention. This study aimed to meet the need for a better and more comprehensive understanding of the awareness, knowledge, and acceptability of PrEP among undergraduate students in Southern Thailand. A cross-sectional survey was conducted among 259 undergraduate students at Walailak University from December 2020 to March 2021. The convenient sampling technique method was used to select the participants. For data analysis, descriptive and inferential statistics were used. According to the study findings, the majority (65%) of the participants were female, and 31.69% of the participants were aged between 18 and 21 years. It was also discovered that 20.8% of the participants had heard of PrEP and that 39.8% were ready to accept the use of PrEP. Furthermore, nearly half of the participants were unable to determine who was eligible for PrEP, and only a small percentage of them were aware of the cost and how to use PrEP. The results of the current setting revealed that participants had a low level of awareness, knowledge, and acceptability of PrEP, despite a high level of intention to use it. Our findings also found that participants who were aware of the existence of PrEP were more likely to accept it than those who were not. Awareness campaigns and public education are required to increase PrEP acceptability in Thailand.
Keywords: Pre-exposure prophylaxis, university students, awareness of existence, acceptability, knowledge